Решите уравнение способом подстановки {3(х+4у)-4х=2(2х+у), {7(х-5у)+ 6х=3(х+4у)+27

Решите уравнение способом подстановки {3(х+4у)-4х=2(2х+у), {7(х-5у)+ 6х=3(х+4у)+27
Гость
Ответ(ы) на вопрос:
Гость
3(x+4y)-4x=2(2x+y) 7(x-5y)+6x=3(x+4y)+27 3(x+4y)-4x=2(2x+y) -x+12y-2*(2x+y)=0 -x+12y-4x-2y=0 -5x+10y=0 -5x+10y=0 y=5x/10 y=0.5x 7(x-5y)+6x=3(x+4y)+27 7(x-5*(0.5x))+6x=3(x+4*(0.5x))+27 7*(-1.5x)+6x-3*(x+4*0.5x)-27=0 -4.5x-3*(x+4*0.5x)-27=0 -4.5x-3*3x-27=0 -4.5x-9x-27=0 -13.5x-27=0 x=-27/13.5 x=-2 3(x+4y)-4x=2(2x+y) 3((-2)+4y)-4*(-2)=2(2*(-2)+y) -6+12y-(-4*2)-2*(2*(-2)+y)=0 -6+12y+8-2*(2*(-2)+y)=0 2+12y-2*(-2*2+y)=0 2+12y-(-8+2y)=0 10+12y-2y=0  10+10y=0 y=-10/10 y=-1 Ответ: x=-2; y=-1.
Гость
[latex] \left \{ {{3(x+4y)-4x=2(2x+y),} \atop {7(x-5y)+ 6x=3(x+4y)+27}} \right.\\ \\ \left \{ {{3x+12y-4x=4x+2y,} \atop {7x-35y+6x=3x+12y+27}} \right.\\ \\ \left \{ {{3x+12y-4x-4x-2y=0,} \atop {7x-35y+6x-3x-12y=27}} \right.\\ \\ \left \{ {{-5x+10y=0,} \atop {10x-47y=27}} \right.\\ \\ \left \{ {{x=\frac{-10y}{-5},} \atop {10x-47y=27}} \right.\\ \\ \left \{ {{x=2y,} \atop {10x-47y=27}} \right.\\ \\ 10*2y-47y=27\\ 20y-47y=27\\ -27y=27\\ y=-1\\ \\ x=2*(-1)=-2[/latex] Ответ: (-2; -1)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы